Vehicle Emergency Service System - Wanarkar, Suwarna; Mahajan, Rohit; Kungwani, Anjali (International Journal of Computer Sciences and Engineering, 2025)
The system of vehicle repair service is a problem that needs to research on the location of repair centres according to the service needs and available resource based on the maximal covering location and priority queuing theory. Considering the effect of waiting time due to rush jobs, this project proposes a model that maximizes the service covering, and restrains. Service level of uncovered zones. As we see people facing many problems related to vehicles and Most of the people use network services and offering online application service in order to create more benefit for users as well as service provider. So we will build the application of Management system with notification using app will be developed to resolve all the current problem related to the vehicle. Using which the person who is looking for vehicle repair service will get all the facilities of the vehicle in their own location. The scope of this project will focus on the user and service provider who will use this application via online service. This project will also be implemented in small stores. The proposed system will save the efforts and time of a user as well as improve the growth of employment.